Efeito antiproliferativo, germinação de sementes e diversidade genética de Hesperozygis ringens (Benth.) Epling (Lamiaceae) - Leite, Leandro Gonçalves (2021)
Hesperozygis ringens is a species belonging to Lamiaceae. This shrub plant is endemic to the Rio Grande do Sul and is located in restricted areas of a few municipalities in the Rio Grande do Sul. Popularly known as "espanta-pulga", it has antiparasitic, anesthetic and allelopathic effects due to the chemical compounds of essential oils. Currently, the species is threatened with extinction and there are few studies related to its conservation. Studies carried out on the biological effects make a plant promising in elaborating natural products for parasite control. This work aimed to genetically and physiologically characterize Hesperozygis ringens to contribute to the conservation of the species. Samples were collected from the municipalities of Santa Maria, Caçapava do Sul, São Francisco de Assis and São Pedro do Sul. The Allium cepa test was used to verify the genotoxicity of H. ringens. The genetic diversity was analyzed using ISSR molecular markers. The statistical analyzes were performed using Sisvar, GenAlEx Structure and PowerMarker softwares. The results showed that the aqueous extracts of H. ringens has an antiproliferative and non-genotoxic effect on Allium cepa roots. The population presented lower genetic diversity indexes, however, they configure genetically well-structured groups. The seeds of H. ringens had higher germination rates in the presence of light and at a temperature of 15 ºC. The search for better reproduction strategies and the preparation of conservation plans for the species and habitats are fundamental.